Clinical significance of ragA, ragB, and PG0982 genes in Porphyromonas gingivalis isolates from periodontitis patients. (5th March 2021) - Bunte, Kübra; Kuhn, Christina; Walther, Carolin; Peters, Ulrike; Aarabi, Ghazal; Smeets, Ralf; Beikler, Thomas
Abstract: Consistent detection of ragA, ragB, and PG0982 in the genome of Porphyromonas gingivalis ( P . gingivalis ) isolates from periodontitis patients suggests that genotypes containing these genes may influence virulence and P . gingivalis ‐associated periodontitis progression. This study evaluated the prevalence of these genes in P . gingivalis isolates from periodontitis patients (n = 28) and in isolates from periodontally healthy P . gingivalis carriers (n = 34). The association of these genes with progression of periodontitis, in vitro cell invasiveness, and bacterial survival following periodontal therapy was also assessed. Periodontal charting and microbiological sampling were done at baseline, and at 6, 12, and 24 months following subgingival debridement of the periodontitis patients. Healthy controls were assessed at baseline for comparison. P . gingivalis isolates were analysed by ragA, ragB, and PG0982 specific polymerase chain reaction (PCR) and Sanger sequencing. Primary human gingival fibroblasts were used for invasion experiments. Results showed that 25% of the tested isolates from the periodontitis group had ragB detected, whereas this gene was undetected in isolates from healthy participants. However, none of the selected genes was associated with an increased cell invasiveness in vitro, with bacterial survival, or with significant clinical periodontal parameter changes. Identification of genes that influence P . gingivalis virulence and therapeutic outcome may have a diagnostic or prognostic value.